Polygenic Ara-C Response Score Identifies Pediatric Patients With Acute Myeloid Leukemia in Need of Chemotherapy Augmentation. Issue 7 (1st March 2022) - Elsayed, Abdelrahman H.; Cao, Xueyuan; Mitra, Amit K.; Wu, Huiyun; Raimondi, Susana; Cogle, Christopher; Al-Mansour, Zeina; Ribeiro, Raul C.; Gamis, Alan; Kolb, Edward Anders; Aplenc, Richard; Alonzo, Todd A.; et al.
Abstract : PURPOSE: To establish a patient-specific polygenic score derived from cytarabine (ara-C) pathway pharmacogenomic evaluation to personalize acute myeloid leukemia (AML) treatment. MATERIALS AND METHODS: Single nucleotide polymorphisms (SNPs) in the ara-C-pathway genes were analyzed with outcome in patients from the multicenter-AML02 trial (N = 166). Multi-SNP predictor modeling was used to develop 10-SNP Ara-C_SNP score (ACS10) using top SNPs predictive of minimal residual disease and event-free survival (EFS) from the AML02-cohort and four SNPs previously associated with ara-C triphosphate levels in the AML97 trial. ACS10 was evaluated for association with outcomes in each clinical trial arms: the standard low-dose ara-C (LDAC, n = 91) and augmented high-dose ara-C (HDAC, n = 75) arms of AML02 and the standard Ara-C, daunorubicin and etoposide (ADE) (n = 465) and the augmented ADE + gemtuzumab ozogamicin (GO; n = 466) arms of AAML0531 trial. RESULTS: In the standard LDAC-arm of AML02 cohort, the low-ACS10 score group (≤ 0) had significantly worse EFS (ACS10 low v high hazard ratio [HR] = 2.81; 95% CI, 1.45 to 5.43; P = .002) and overall survival (OS; HR = 2.98; 95% CI, 1.32 to 6.75; P = .009) compared with the high-ACS10 group (score > 0). These results were validated in the standard-ADE arm of AAML0531, with poor outcome in the low-ASC10 group compared with the high-ACS10 group (EFS: HR = 1.35, 95% CI, 1.04 to 1.75, P = .026; OS: HR = 1.64, 95% CI, 1.2 to 2.22, P = .002). Within the augmented arms (AML02-HDAC and AAML0531-ADE + GO), EFS and OS did not differ between low- and high-ACS10 score groups. In both cohorts, patients with low-ACS10 consistently showed a 10-percentage point improvement in 5-year EFS with augmented therapy (AML02-HDAC or AAML0531-ADE + GO arms) than with standard therapy (AML02-LDAC or AAML0531-ADE arms). CONCLUSION: Patients with low-ACS10 score experienced significantly poor outcome when treated on standard regimen. Augmentation with either high-dose ara-C or GO addition improved outcome in low-ACS10 group. A polygenic ACS10 score can identify patients with unfavorable pharmacogenetic characteristics and offers a potential for an elective augmented therapy option. Abstract :